Let's break down the expression \(-3^0 + 4.5\) step by step.
-
Evaluate \(-3^0\):
- Any number (except zero) raised to the power of 0 is 1.
- Therefore, \(-3^0 = -1\).
-
Combine with \(4.5\):
- Now we have \(-1 + 4.5\).
-
Calculate:
- \(-1 + 4.5 = 3.5\).
Now, let’s review the options given:
-
-3^0 + 4.5 = -1.3^0 + 4.5 = -1.1 + 4.5 = -1 + 4.5 = 3.5
- The first part is incorrect because it incorrectly states \(-1.3^0\) instead of correctly calculating \(-3^0\). However, the final result \(3.5\) is correct.
-
-3^0 + 4.5 = -3^0 + 4.5 = 1 + 4.5 = 1 + 4.5 = 5.5
- This is incorrect because it mistakenly states \(-3^0 = 1\) instead of \(-3^0 = -1\).
-
-3^0 + 4.5 = -3 + 4.5 = 1.5
- This is incorrect because it incorrectly replaces \(-3^0\) with \(-3\).
-
-3^0 + 4.5 = -3.0 + 4.5 = 0 + 4.5 = 4.4
- This is incorrect, as it mistakenly evaluates \(-3^0\) as \(-3.0\).
Thus, while the first option has a calculation error in steps leading to \(3.5\), it is the only one that arrives at the correct final answer, which is \(3.5\).
The correct choice based on the final result is the first option, albeit with an initial error.